2015
DOI: 10.1105/tpc.114.132787
|View full text |Cite
|
Sign up to set email alerts
|

MET1 Is a Thylakoid-Associated TPR Protein Involved in Photosystem II Supercomplex Formation and Repair in Arabidopsis

Abstract: ORCID ID: 0000-0001-9536-0487 (K.J.v.W.)Photosystem II (PSII) requires constant disassembly and reassembly to accommodate replacement of the D1 protein. Here, we characterize Arabidopsis thaliana MET1, a PSII assembly factor with PDZ and TPR domains. The maize (Zea mays) MET1 homolog is enriched in mesophyll chloroplasts compared with bundle sheath chloroplasts, and MET1 mRNA and protein levels increase during leaf development concomitant with the thylakoid machinery. MET1 is conserved in C3 and C4 plants and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(61 citation statements)
references
References 108 publications
(164 reference statements)
3
58
0
Order By: Relevance
“…S6, S11, and S14). Our data are consistent with published reports that-under growth chamber fluctuating light conditions-tlp18.3, psb27, and met1-2 displayed stunted growth phenotypes (29,40,42,45). Moreover, reduced greenhouse growth is not simply the result of lower PSII efficiency.…”
Section: Psii Repair Mutants Are Defective In Growth Acclimation Undersupporting
confidence: 83%
See 2 more Smart Citations
“…S6, S11, and S14). Our data are consistent with published reports that-under growth chamber fluctuating light conditions-tlp18.3, psb27, and met1-2 displayed stunted growth phenotypes (29,40,42,45). Moreover, reduced greenhouse growth is not simply the result of lower PSII efficiency.…”
Section: Psii Repair Mutants Are Defective In Growth Acclimation Undersupporting
confidence: 83%
“…S14 A and B), as previously reported (30,31,42,43). In contrast, these mutants displayed reduced growth and PSII activity in the greenhouse (SI Appendix, Fig.…”
Section: Mph2 Promotes Psii Protein Subunit Turnover and Interacts Wisupporting
confidence: 55%
See 1 more Smart Citation
“…Other TPR domain-containing proteins among the 147 in Arabidopsis, including SHORT AND SWOLLEN ROOT1 and MET1, localize to mitochondria and chloroplasts, respectively, consistent with their functions in oxidative stress-mediated root development and in the assembly of the photosynthetic apparatus (Bhuiyan et al, 2015;Zhang et al, 2015). The TPR protein CLUMPED CHLOROPLAST1 (CLMP1) localizes to distinct foci in the cytoplasm.…”
Section: Hlb1 Is a Component Of The Plant Post-golgi Trafficking Machmentioning
confidence: 73%
“…TPR domains mediate protein-protein interactions, and proteins containing these domains are part of protein complexes with diverse functions including transcriptional repression, protein import, heat shock, and cell cycle regulation (Blatch and Lässle, 1999;D'Andrea and Regan, 2003). TPR domaincontaining proteins in plants have been implicated in responses to various hormones, assembly of the photosynthetic machinery, plastid partitioning, and root development (Jacobsen et al, 1996;Rosado et al, 2006;Yang et al, 2011;Hu et al, 2014;Bhuiyan et al, 2015). Confocal microscopy of cells from the elongation zone and root hairs of hlb1-1 seedlings expressing HLB1pro:HLB1-GFP revealed that the fusion protein localized to the cytoplasm and decorated distinct and dynamic foci (Figures 6C and 6D; Supplemental Movie 4).…”
Section: Hlb1 Is a Tetratricopeptide Repeat-containing Protein Encodementioning
confidence: 99%